Elements of discrete mathematics : A computer oriented approach - Liu, C. L.; Mohapatra, D. P. (New Delhi: Tata McGraw Hill Education, 2008)
This book, intended for a 3rd/4th Semester course on Discrete Mathematics, presents the subject in an algorithmic point of view without adhering to any particular language. The subject has been treated using concepts and solved examples juxtaposed against each other.
Index 545-547p.
Keywords: Discrete mathematics; Mathematics; Sets; Computer Science